Pengaruh Motivasi dan Komitmen Terhadap Prestasi Kerja Karyawan Manise Hotel di Ambon - Paais, Maartje (Akutansi Bisnis & Manajemen ( ABM ), 2017)
Research was conducted on Manise Hotel in Ambon. This study uses the motivation and commitment of employees as independent variables, and job performance as the dependent variable. The purpose of this study to analyze and determine the effect of motivation and commitment of employees on work performance and determine the dominant influence between the variables of motivation and commitment of employees on work performance. The samples are employees Manise Hotel Ambon with a total sample of 47 respondents. Based on the above results it can be seen that: (1) Motivation and employee commitment significant and positive impact on employee performance, high motivation with employee commitment will lead to improved employee performance Manise Hotel in Ambon; (2) It can be seen that motivation is a free variable that has dominant influence on achievement compared with other independent variables; and (3)Motivation and commitment to jointly contribute / donations by 58.2% to changes in job performance, while the remaining 41.8% is the donation / contribution of other variables that are not observed in this study, for example stress of work, compensation, leadership style, culture work and discipline